Hubungan antara Fertilitas, Mortalitas, dan Migrasi dengan Laju Pertumbuhan Penduduk - Ainy, Hidayatul; Nurrochmah, Siti; Katmawanti, Septa (Preventia: The Indonesian Journal of Public Health, 2019)
The low rate of population growth in Klojen Districts, cause the population in the region continues to decrease. Reduced population will affect the availability of human resources in the Klojen District. Therefore, conducted a study entitled "The relationship between Fertility, Mortality and Migration with Population Growth Rate”. The purpose of this study was to determine the effect of fertility, mortality and migration to the rate of population growth. This type of research is an explanatory survey. Subjects in this study amounted to 11 urban villages. Data collection using documentation data. Data analysis technique used is a Rank Order technique from Spearman. The results of this study indicate that: (1) The value ρ arithmetic of fertility 0.67 > value ρ table 0.591. (2) The value ρ arithmetic of mortality 0.44 < value ρ table 0.591. (3) The value ρ arithmetic of in-migration 0.12 < value ρ table 0.591. (4) The value ρ arithmetic of out-migration -0.08 < value ρ table 0.591. The conclusion of this study: (1) there is a significant relationship between fertility with population growth rate. (2) there is no significant relationship between mortality, in-migration , and out-migration with population growth rate.